Mycobacterium tuberculosis bacilli in oral biopsies containing granulomatous inflammation with caseous necrosis - Oliveira Signoretti-Silva, Rubens; Santiago Gomez, Ricardo; Gonçalves Diniz, Marina; Spíndola de Miranda, Silvana; Santana Aguiar, Renato; Jouca de Assis Figueredo, Lida; Araújo Buzelin, Marcelo; Lima Araújo, Thaís; Bernardes, Vanessa (Journal of Oral Diagnosis, 2024)
Objetive: This cross-sectional and retrospective study aimed to investigate the presence of Mycobacterium tuberculosis bacillus in formalin-fixed paraffin-embedded (FFPE) oral samples that contained granulomas with caseous necrosis. Methods: FFPE biopsies that showed granulomas with caseous necrosis, suggestive of the diagnosis of tuberculosis, were selected. M. tuberculosis was searched by Ziehl-Neelsen staining (ZN), immunohistochemistry (IHC), nested-PCR, and GeneXpert® MTB/RIF assays. Results: Nine samples showing granulomas with caseous necrosis were selected. The study showed a male predominance, with a ratio of 2.5:1, with a mean age of 50 (19-89) years, and the tongue was the most affected anatomical site (n=4). The ZN technique did not detect bacilli in any sample, and IHC staining showed a coarse granular pattern staining, suggestive of M. tuberculosis, in three of them. Nested-PCR and the GeneXpert® MTB/RIF assays were positive in two and three of the samples, respectively. Conclusion: Molecular tests and IHC may be useful auxiliary methods for suspected cases of oral tuberculosis.